2020
DOI: 10.3390/cells9020417
|View full text |Cite
|
Sign up to set email alerts
|

Human Plasmacytoid Dendritic Cells and Cutaneous Melanoma

Abstract: The prognosis of metastatic melanoma (MM) patients has remained poor for a long time. However, the recent introduction of effective target therapies (BRAF and MEK inhibitors for BRAFV600-mutated MM) and immunotherapies (anti-CTLA-4 and anti-PD-1) has significantly improved the survival of MM patients. Notably, all these responses are highly dependent on the fitness of the host immune system, including the innate compartment. Among immune cells involved in cancer immunity, properly activated plasmacytoid dendri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 287 publications
0
40
0
Order By: Relevance
“…DCs are endowed with a high functional plasticity allowing them to orientate immune responses towards diverse profiles depending on the microenvironment. Tumors exploit such versatility of DCs through suppressive pathways to subvert DC functions and escape immunity 22‐25 . Despite evidence of tumor infiltration by the three DC subsets, 26‐30 their precise pathophysiologic role remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…DCs are endowed with a high functional plasticity allowing them to orientate immune responses towards diverse profiles depending on the microenvironment. Tumors exploit such versatility of DCs through suppressive pathways to subvert DC functions and escape immunity 22‐25 . Despite evidence of tumor infiltration by the three DC subsets, 26‐30 their precise pathophysiologic role remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…As previously reported, circulating pDCs are reduced in various human cancer patients compared to healthy subjects, particularly in the advanced stage of disease [ 35 ]. By flow cytometry on fresh whole blood, we previously documented the collapse of pDC and myeloid DC (mDC) subsets in advanced MM [ 29 ].…”
Section: Resultsmentioning
confidence: 67%
“…The frequency of circulating pDCs is dramatically reduced in melanoma patients with systemic spread [ 29 , 52 , 53 ], but their clinical significance as well as their functional state have been poorly characterized [ 35 ]. Findings from retrospective analysis are conflicting [ 35 ]. This study reports the analysis of the circulating pDCs in a prospective chemo-naïve MM patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Some have suggested that the addition of novel innate cell-based therapies could overcome radiation-induced immunosuppressive effects [35] through their activation of Toll-like receptors. One such receptor, TLR9, is expressed in pDCs and stimulates antitumor immunity by producing IFNs [36] . Mature pDCs are also known to prime antigen-specific T-cell immunity through response to a variety of DNA and RNA viruses [37] .…”
Section: Discussionmentioning
confidence: 99%